2022
DOI: 10.1002/tox.23446
|View full text |Cite
|
Sign up to set email alerts
|

Lithium intoxication induced pyroptosis viaROS/NF‐κB/NLRP3inflammasome regulatory networks in kidney of mice

Abstract: Humans and animals may be exposed to increasing contaminant lithium (Li) concentrations in the environment with the use and disposal of Li-containing products.Meanwhile, Li plays a key role in the treatment of human mental disorders, while the excessive accumulation of Li salts in the body can cause renal damage and nephrotic syndrome. In this study, the mechanism of renal inflammatory reaction induced by Li excessive intake was studied by establishing mice models in vitro and in vivo. The results of histopath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…34 Organ fibrosis is an internal body resistance process to chronic external injury and is involved in fibroblast to myofibroblast activation and differentiation, along with the EMT program. 35 Evidence has proven that chronic exposure to a series of chemicals in the environment, including lithium, 36 cadmium, 37 industrial dust, 38 melamine, 39 and crystalline silica, 40 can increase the level of fibrosis-related proteins and promote EMT development in the kidney, which results in renal fibrosis. Although the universal herbicide ATR, with its low toxicity, has been used for more than 50 years, concerns regarding its adverse effects have been increasing.…”
Section: Discussionmentioning
confidence: 99%
“…34 Organ fibrosis is an internal body resistance process to chronic external injury and is involved in fibroblast to myofibroblast activation and differentiation, along with the EMT program. 35 Evidence has proven that chronic exposure to a series of chemicals in the environment, including lithium, 36 cadmium, 37 industrial dust, 38 melamine, 39 and crystalline silica, 40 can increase the level of fibrosis-related proteins and promote EMT development in the kidney, which results in renal fibrosis. Although the universal herbicide ATR, with its low toxicity, has been used for more than 50 years, concerns regarding its adverse effects have been increasing.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 NLRP3 inflammasome-related pyroptosis is one of the NF-κB-mediated cell death modes and is a regulated form of necrosis. 24 It has been shown that exposure to 5 μm polystyrene microplastics (PS-MPs) induces reactive oxygen species (ROS) overload in chicken hearts, which, in turn, induces pyroptosis through the NF-κB/NLRP3/GSDMD pathway. 25 Furthermore, polystyrene nanoparticles (PSNPs) can aggravate the duodenal inflammatory reaction of mice through the ROS-activating NF-κB/NLRP3 pathway, and NF-κB inhibitor QNZ can significantly reduce the expression of NLRP3 inflammasome.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress occurs when mitochondria are damaged due to reduced mitochondrial fusion, increased fission, and impaired biogenesis . Abnormalities in mitochondrial division and fusion caused by some noxious stimuli or pathological conditions can lead to imbalances in mitochondrial dynamics, and the resulting oxidative damage is associated with activation of the NF-κB pathway and NLR family pyrin domain-containing 3 (NLRP3) inflammatory inflammasome. , NLRP3 inflammasome-related pyroptosis is one of the NF-κB-mediated cell death modes and is a regulated form of necrosis . It has been shown that exposure to 5 μm polystyrene microplastics (PS-MPs) induces reactive oxygen species (ROS) overload in chicken hearts, which, in turn, induces pyroptosis through the NF-κB/NLRP3/GSDMD pathway .…”
Section: Introductionmentioning
confidence: 99%
“…2,3 For instance, the lithium element in waste cathode materials will directly enter the soil environment and accumulate excessively in the body through the food chain, thereby causing kidney damage and nephrotic syndrome that threatening human health. 4 On the other hand, lithium is also an important industrial raw material and strategic resource. 5 If it flows into the environmental medium without resource treatment, it will undoubtedly exacerbate the current situation of resource shortage.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Meanwhile, lithium-ion batteries (LIBs) pervade all aspects of our lives, and their demand is growing rapidly. Although their wide application has alleviated the environmental pollution problems caused by traditional energy sources, they also has adverse effects. , For instance, the lithium element in waste cathode materials will directly enter the soil environment and accumulate excessively in the body through the food chain, thereby causing kidney damage and nephrotic syndrome that threatening human health . On the other hand, lithium is also an important industrial raw material and strategic resource .…”
Section: Introductionmentioning
confidence: 99%